Il piccolo Pantheon I grandi autori in scena sul teatro francese tra Settecento e Ottocento - INNOCENTI, BARBARA (Biblioteca di Studi di Filologia Moderna, 2018)
In Paris, the Little Pantheon is the theatre on rue de Chartres which, together with other showrooms, competed with the great Pantheon on rue Soufflot between the 18th and 19th century. The Little Pantheon introduced the idea of a Big Man embracing the excluded personalities from the official Pantheon, and those categories, such as the actors, which had been hitherto marginalised. This volume takes into consideration a new theatrical genre bringing on stage the public and private lives of Great Men of Letters, Philosophy and the Arts, be them real or imaginary. This book is not only original for its analysis of the revolutionary mentality that shapes a new concept of Fame, but also functions as a tool to account for the extent of the phenomenon from a chronological and thematic perspective thanks to the Catalogues.